CTHRC1: a key player in colorectal cancer progression and immune evasion - Chen, Qingjie; Wang, Haohao; Liu, Qinghua; Luo, Changjiang (Frontiers in Immunology, 2025)
The multifunctional secreted protein, collagen triple helix repeat containing 1 (CTHRC1), has recently emerged as a significant focus within oncology research. CTHRC1 expression in tumors is governed by a complex interplay of regulatory signals, including methylation, glycosylation, and notably, non-coding RNAs, which constitute its predominant regulatory mechanism. Colorectal cancer (CRC), a highly prevalent epithelial malignancy, sees CTHRC1 influencing tumor progression and metastasis through its modulation of several downstream signaling cascades, such as Wnt/PCP, TGF-β/Smad, and MEK/ERK pathways. Furthermore, CTHRC1 contributes to immune evasion in CRC via diverse mechanisms. It is intricately associated with macrophage phenotypic switching within the tumor microenvironment (TME), favoring M2 macrophage polarization and facilitating the infiltration of T cells and neutrophils. CTHRC1 is also instrumental in immune escape by driving the remodeling of the extracellular matrix through interactions with cancer-associated fibroblasts. Additionally, CTHRC1’s roles extend to the regulation of hypoxia-related pathways, metabolism of glycolysis and fatty acids, and involvement in tumor angiogenesis, all of which support tumor immune evasion. Considering its multifaceted activities, CTHRC1 emerges as a promising therapeutic target in CRC, with the potential to enhance the outcomes of existing radiotherapeutic and immunotherapeutic regimens. This review endeavors to delineate the mechanistic and therapeutic landscapes of CTHRC1 in CRC. Through a comprehensive discussion of CTHRC1’s diverse functions, we aim to provide insights that could pave the way for innovative approaches in cancer therapy.